EFEKTIFITAS DAN EFISIENSI PENYELESAIAN SENGKETA EKONOMI SYARIAH DI PERADILAN AGAMA - Hasanuddin Muhammad (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2020)
The era of the industrial revolution 4.0 has brought great changes to the human. The Supreme Court as the highest judicial body should embody effective and efficient justice with the simple, fast, and low cost princeples. This study examines the extent to which the Supreme Court Regulations regulate and embody an effective and efficient judicial system in resolving Islamic economic disputes in religious courts. This type of research is qualitative with a normative juridical approach. As a result, the Supreme Court has issued several rules as an effort to embody an effective and efficient judiciary, namely Supreme Court Regulation Number 2 of 2015 concerning the procedure for simple lawsuit resolution, Supreme Court Regulation Number 14 of 2016 concerning Procedures for Settling Sharia Economic Disputes, Regulation of the Supreme Court Number 5 year 2016 concerning Sharia Economic Judge Certification, Supreme Court Regulation 04 of 2019 concerning amendment to Supreme Court Regulation Number 02 of 2015 concerning Simple Settlement Procedures and Supreme Court Regulations 01 of 2019 concerning Electronic Case and Trial Administration. It regulates efforts to embody the resolution for Sharia economic disputes that are effective and efficient, namely through a simple lawsuit, judges must have competence in the field of sharia economics by issuing a sharia economic judge certification policy and providing judicial services electronically.